Low-dose Bisphenol A and its analogues Bisphenol F and S activate estrogen receptor ß and slightly modulate genes in human gingival keratinocytes. Issue 4 (April 2021) - Burkhardt, Felix; Schulz, Simon Daniel; Hellwig, Elmar; Vach, Kirstin; Tomakidi, Pascal; Polydorou, Olga
Highlights: Bisphenol F and S show comparable hormonal properties to Bisphenol A. Estrogen receptor ß in gingival keratinocytes is activated by Bisphenol A, F and S. Bisphenol A and its analogues induce only marginal modulations of gene expression. Abstract: Objectives: This study investigated the putative activation of estrogen receptor β (ERβ) and possible effects related on gene expression in oral mucosal cells in response to the endocrine disruptor Bisphenol A (BPA) and its analogues Bisphenol F (BPF) and Bisphenol S (BPS). Methods: Human gingival keratinocytes (HGK) were exposed to BPA-, BPF-, and BPS-solutions in concentrations of 1.3 μM, 0.16 μM and 11.4 nM as well as 200 pM and 100 nM estradiol (E2 ) for 6 h, 24 h and 4 d. Indirect immunofluorescence (IIF) was performed to detect a possible ERβ activation. Additionally, transcription of keratinocyte-relevant biomarkers was analyzed by quantitative real-time PCR (qRT-PCR). A linear mixed model and pairwise comparisons were applied for statistical analyses. Results: The tested concentrations of BPA, BPF, BPS and E2 revealed distinct activation of ERβ at all time periods, whereat 100 nM E2 induced the most pronounced activation. Despite the detected ERβ activation, the concentrations of BPA and its analogues induced only moderate modulation of the tested keratinocyte-relevant biomarker genes at all time periods. This also applied to 200 pM E2, while in case of 100 nM E2 significant changes (p < 0.05) were detected for almost all analyzed genes. Significance: Though BPA and its analogues induce activation of ERß irrespective from the chosen concentrations and incubation periods, they lack significant modulation of gene expression of keratinocyte-relevant biomarkers. Although limited to a selected number of genes, the sparse modulation of gene expression may give a hint that the substances do slightly affect transcription of gingival-keratinocyte-innate genes, since the concentrations applied to HGK were of physiological importance.